Water deficit is increasingly limiting vegetation productivity in China - Hanshi Sun; Yongming Cheng; Liu Liu; Qiang An; Hongbo Zhang (Ecological Indicators)
Although there is an increasing interest in forecasting global and regional vegetation productivity trends under climate change, it remains unclear whether the effects of water availability on vegetation growth are changing. This study evaluates the long-term trends and time thresholds (the time required for vegetation to respond to changes in water availability) in vegetation productivity under water constraints (both deficit and surplus) in China from 1982 to 2018. The results, based on an analysis of two remote sensing datasets, demonstrated that over 50 % of China’s terrestrial ecosystems experienced increasing water constraints on vegetation productivity. A total of 54.19 % and 55.82 % of vegetation areas exhibited significant inhibition of vegetation photosynthesis due to water deficit, while 20.71 % and 21.25 % of vegetation areas experienced significant inhibition of photosynthesis due to water surplus based on GLASS and MuSYQ datasets from 1982 to 2018. The minimum time thresholds for vegetation productivity’s response to water deficit decreased by −0.94 months/decade and −1.52 months/decade, while the maximum time thresholds for vegetation productivity’s response to water surplus increased by 1.29 months/decade and 1.58 months/decade. This suggests that it is easier to suppress vegetation productivity with a water deficit and more difficult with a water surplus, and that vegetation productivity is increasingly affected by water deficit. This study identifies the evolving trends in the impact of water availability on vegetation growth within the context of global climate change, offering a scientific foundation for understanding the water–carbon coupling relationship and the water–carbon cycle.